2013
DOI: 10.1007/s00520-013-2051-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical instillations with polydeoxyribonucleotides reduce symptoms of radiation-induced cystitis in patients treated with radiotherapy for pelvic cancer: a pilot study

Abstract: Subjective perception of persistent and/or worsening CRC symptoms, despite conventional therapy, is improved after intravesical instillation with PDRNs without adverse events. Even though we deduced suggestive insights, the results need to be collected and verified from a large-scale study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
2
1
3
Order By: Relevance
“…Evidence for their use in radiation cystitis is sparse. One small prospective observational cohort study of eight patients with late radiation cystitis suggested an improvement in reported cystitis symptoms following biweekly PDRN bladder instillations for two months [ 25 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Evidence for their use in radiation cystitis is sparse. One small prospective observational cohort study of eight patients with late radiation cystitis suggested an improvement in reported cystitis symptoms following biweekly PDRN bladder instillations for two months [ 25 ].…”
Section: Treatmentmentioning
confidence: 99%
“…PDRN also showed positive effects on RT-induced cystitis. 73 PDRN was intravesically instilled biweekly for 2 months in eight patients (CRC) previously subjected to RT for pelvic cancer with chronic radiation cystitis unresponsive to conventional medical treatment. Four months after the last infusion, hematuria, which is characteristic of hemorrhagic cystitis, and CRC symptoms significantly improved.…”
Section: Pdrn and The Regulation Of Inflammation: Clinical Endpointsmentioning
confidence: 99%
“…Внутрипузырное введение лекарственных средств осуществлялось с помощью Ботулотоксина А, получено увеличение объема мочевого пузыря, снижение частоты мочеиспускания с 14 до 11, отсутствие побочных реакций; гиалуроновой кислоты, при этом наблюдали значительное уменьшение частоты позывов к мочеиспусканию, значительное уменьшение болевого синдрома, побочные эффекты: увеличение инфицированности мочевыводящих путей к 6 месяцам; хондроитина сульфатом, с положительным эффектом снижения симптомов в жалобах пациентов, побочных эффектов не описано. Некоторые авторы описали результат лечения полидезоксирибонуклеотидами -уменьшение симптомов цистита; формалина со значительным уменьшением кровотечения, однако с высоким уровнем осложнений вплоть до смертельных; а также ранним плацентарным экстрактом, сопровождалось уменьшением симптомов цистита, цистоскопически подтвержденных [37,38].…”
unclassified
“…Bonfili и соавт. [37] на очень ограниченном материале провели исследования влияния нитрата серебра, обладающего антисептическими и вяжущими качествами, получив обнадеживающие результаты. Однако авторы считают, что осложнения у пациентов с радиационными циститами связаны с нарушением функции почек и анурией.…”
unclassified